2002
DOI: 10.1128/aem.68.5.2600-2604.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glucose in Enhancing the Temperature-Dependent Growth Inhibition ofEscherichia coliO157:H7 ATCC 43895 by aPseudomonassp

Abstract: Growth of Escherichia coli O157:H7 strain ATCC 43895 was monitored at 5, 10, 15, and 25°C in both pure and mixed (1:1) cultures with a gluconate-producing Pseudomonas sp. found in meat to evaluate the effect of the absence and presence of 1% glucose in broth on temperature-dependent competition. The number of colonies of the Pseudomonas strain exceeded 9 log CFU/ml under all conditions tested. The pathogen grew better as the temperature increased from 10 to 15 and 25°C and grew better in pure culture than in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…2 d, and a ttr 8 log of 3.5-3.7 d. These authors(Samelis & Sofos, 2002) did not detect changes in pH along the incubation period (14 d) irrespective of the temperature and the type of culture: pH values of 7.3-7.4; in contrast, pH reductions were pronounced when 1% of glucose was added to the medium decreasing to values of 5.0-6.0. The pH values in single cultures or in co-cultures in our study decreased along the study from 6.7-6.8 to about 6.5 after 28 d at 7 or 13 ºC (data not shown).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…2 d, and a ttr 8 log of 3.5-3.7 d. These authors(Samelis & Sofos, 2002) did not detect changes in pH along the incubation period (14 d) irrespective of the temperature and the type of culture: pH values of 7.3-7.4; in contrast, pH reductions were pronounced when 1% of glucose was added to the medium decreasing to values of 5.0-6.0. The pH values in single cultures or in co-cultures in our study decreased along the study from 6.7-6.8 to about 6.5 after 28 d at 7 or 13 ºC (data not shown).…”
mentioning
confidence: 71%
“…did not reach 6 or 8 log CFU/ml at 7 ºC. Samelis & Sofos (2002) found that E. coli O157:H7 co-cultured at 15 ºC with Pseudomonas reached populations of 6 or 8 log CFU/ml after ~0.5 or 2 d, respectively and when the co-cultures were supplemented with 1% of glucose E. coli O157:H7 achieved populations of 6 or 8 log CFU/ml after ~1.2 or 7 d, respectively. We found slightly slower growth in our study at 13 ºC with a ttr 6 log of 1.6-2.…”
Section: But Without Differences Between Low and High Temperatures Asmentioning
confidence: 89%
See 1 more Smart Citation
“…Its production of extracellular gluconate (Lynch and Franklin, 1978), proteinase (Jaspe et al, 1995b), and cytotoxic agents (Picot et al, 2004) has been found to be greater at 7 to 8°C than at higher temperatures. Interference of planktonic Listeria monocytogenes (Farrag and Marth, 1989) and Escherichia coli (Samelis and Sofos, 2002) by Pseudomonas strains has also been reported to be temperature-dependent.…”
Section: Ecological Interactions and Relevance For Milk Qualitymentioning
confidence: 99%
“…The addition of Glucose and Mg 2+ will give a longer phase of E. coli growth (Nikaido, 2009). Culture temperature of 37 o C gives more quick growth of E. coli subsequently it could down growth very fast (Samelis & Sofos, 2002). It might be correlated with the availability of energy source from glucose.…”
Section: Optical Densitymentioning
confidence: 99%